Remark on the muonium to antimuonium conversion in a 3-3-1 model - Pleitez, V. [UNESP] (American Physical Society (APS), 2000)
Here we analyze the relation between the search for muonium to antimuonium conversion and the 3-3-1 model with doubly charged bileptons. We show that the constraint on the mass of the vector bilepton obtained by experimental data can be evaded even in the minimal version of the model since there are other contributions to that conversion. We also discuss the condition for which the experimental data constraint is valid. ©2000 The American Physical Society.